2021
DOI: 10.1038/s41598-021-96697-7
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine prevents amyloid-β secretion in neurons derived from human pluripotent stem cells with trisomy 21

Abstract: Down syndrome (DS) is caused by the trisomy of chromosome 21. Among the many disabilities found in individuals with DS is an increased risk of early-onset Alzheimer's disease (AD). Although higher oxidative stress and an upregulation of amyloid β (Aβ) peptides from an extra copy of the APP gene are attributed to the AD susceptibility, the relationship between the two factors is unclear. To address this issue, we established an in vitro cellular model using neurons differentiated from DS patient-derived induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Additionally, the role of oxidative damage and disulfide bond formation in tau [ 441 ] and other SCCPs are critical triggering mechanisms leading to neurodegenerative disorders and pathogenic progression factors. Therefore, NAC may offer an effective therapeutic strategy to decrease the generation and spread of pathological proteins [ 442 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Additionally, the role of oxidative damage and disulfide bond formation in tau [ 441 ] and other SCCPs are critical triggering mechanisms leading to neurodegenerative disorders and pathogenic progression factors. Therefore, NAC may offer an effective therapeutic strategy to decrease the generation and spread of pathological proteins [ 442 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Directed differentiation of DS NPCs to mixed cortical neurons is associated with impaired maturation and synaptic deficits ( Weick et al, 2013 ; Hibaoui et al, 2014 ) ( Table 1 ). Further, elevated oxidative stress ( Weick et al, 2013 ; Dashinimaev et al, 2017 ; Sobol et al, 2019 ; Toshikawa et al, 2021 ), increased cell death, and pathological hallmarks of AD such as elevated amyloid-ß and hyperphosphorylated tau ( Shi et al, 2012a ; Dashinimaev et al, 2017 ; Toshikawa et al, 2021 ) have also been observed in DS iPSC-derived neurons ( Table 1 ). Transcription factor-driven ( NGN2 ) neuronal differentiation resulted in increased apoptosis of T21 neurons that was associated with dysregulated protein homeostasis and upregulation of endoplasmic reticulum stress pathway ( Hirata et al, 2020 ).…”
Section: Ipsc-derived Neuronsmentioning
confidence: 99%
“…Oxidative injury and disulfide bridges in tau and other SCCPs are crucial pathogenic factors [266], and APOE4 and tau implication in PD dementia has lately been identified [267]. Hence, targeting the cysteine redox proteome is a potential preventive strategy against PD initiation and evolution [268].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%